STRATEGI PEMBERDAYAAN PETANI PAJALE BERBASIS GENDER DI PROVINSI BANTEN - Asih Mulyaningsih; Rita Nur Suhaeti; Nanik Anggoro Purwatiningsih (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
Gender-based Pajale Farmer Empowerment Strategy in Banten Province. Empowerment of farmers in agriculture is a key factor that is indispensable so that farmers are able to play a major role in the management of agricultural resources. The objectives of the research were to: (1) analyze Pajale farmer’s empowerment level; (2) analyze influencing factors on gender-based Pajale farmer’s empowerment level; and (3) design a gender-based Pajale farmer’s empowerment strategy. Field data collection had been conducted for three months, during April and June 2019. Research sites were in Pandeglang and Lebak Distericts, Banten Province, because the two districts were production centers for rice, corn and soybean. Research samples covered 216 farmer households, comprised of 216 husbands and 216 wives. Smart PLS was applied in data analysis. The reserach results showed that: (1) female Pajale farmer’s empowerment level was lower than that of male’s; (2) the influencing factors of male Pajale farmer’s empowerment were participation, empowerment intensity, supports for physical and socio-economic, and the influencing factors of female Pajale farmer’s empowerment were participation; (3) strategy formulation for empowering male and female Pajale farmers were to improve participation in farming activity planning, implemention, and evaluation. The Pajale farmer’s gender-based empowerment strategies were divided into two strategies namely short-term strategies and long-term strategies. The male and female farmers’ empowerment in Pajale farming of Pandeglang and Lebak Distericts could be improved by involving them in their farming activity planning, implemention, and evaluation.Keywords: Gender, Empowerment, StrategyAbstrakPemberdayaan petani baik laki-laki maupun perempuan dalam bidang pertanian, menjadi faktor kunci yang sangat diperlukan agar petani mampu memerankan sebagai pelaku utama dalam pengelolaan sumber daya pertanian. Tujuan penelitian ini adalah menganalisis tingkat keberdayaan, faktor-faktor yang berpengaruh terhadap tingkat keberdayaan, dan merancang strategi pemberdayaan petani Pajale berbasis gender. Pengambilan data dilakukan bulan April sampai Juni 2019. Lokasi penelitian di Kabupaten Pandeglang dan Kabupaten Lebak, Provinsi Banten yang merupakan daerah sentra tanaman padi, jagung, dan kedele (Pajale). Sampel penelitian yang diambil berjumlah 216 rumah tangga petani (suami 216 dan 216 istri). Analisis data dengan menggunakan Smart PLS. Hasil penelitian menunjukkan bahwa tingkat keberdayaan petani perempuan lebih rendah daripada tingkat keberdayaan petani laki-laki. Keberdayaan petani perempuan rendah karena kurang dilibatkan dalam penyuluhan pertanian dan perempuan tidak terdaftar sebagai anggota kelompok tani. Faktor-faktor yang berpengaruh terhadap keberdayaan petani Pajale laki-laki yaitu partisipasi, intensitas pemberdayaan, dan dukungan lingkungan fisik dan sosial ekonomi, sedangkan pada petani Pajale perempuan adalah partisipasi. Strategi keberdayaan petani Pajale (laki-laki dan perempuan) dilakukan dengan meningkatkan partisipasi dalam perencanaan, pelaksanaan, dan evaluasi kegiatan usahatani yang dilakukan pada jangka pendek dan jangka panjang.Kata Kunci: Gender, Pemberdayaan, Strategi